Influence of Social Media on the Business Processes of Corporate Organisation - Omolara Oluwabusayo Akin-Odukoya (Britain International for Academic Research (BIAR) Publisher, 2024)
The integration of social media into business strategies has become an indispensable component for fostering customer engagement, enhancing brand awareness, and optimizing internal processes. As digital transformation continues to reshape industries, social media stands as a crucial pillar in advancing corporate objectives and staying competitive in an increasingly dynamic market. This study aimed to explore the opportunities social media gives to corporate organizations in their business process using, Nigerian Commercial banks as a case study. To achieve this objective, the study examined the Technology Adoption Theory (TAM) which explained that behavioral intention to use leads to actual IT usage behavior and attitude-intention-behavior connection predicts user acceptance of new technologies. By examining different literatures it was ascertained that Social media enables companies to increase knowledge flow between all areas of the company by allowing employees an increased support system of variable knowledge and skill sets, social media provides several options for increasing brand exposure, reaching heterogeneous groups, and creating identity, it enables commercial banks to enhance customer engagement and interaction using content marketing and storytelling as well as enable these organizations handle crises and restore their images in the public eye. In conclusion, the use of social media in corporate organizations, particularly in the banking sector, offers immense potential for growth and innovation. However, organizations must also be mindful of the risks and challenges associated with social media use and develop strategies to mitigate these risks.